Heritage Evaluation: restoration plan through HBIM and MCDA. Issue 1 (November 2020) - Acampa, G; Grasso, M
Abstract: This study is prompted by the activity carried out within a EU funded project (WARMEST)[1] whose goal is to analyze monuments' degradation due to factors such as climate change and growing number of tourists, create a model to describe and anticipate the phenomena, and put in place a user-friendly Decision Support System that will help in setting preventive maintenance plans. As part of the project, we had the chance to study in depth the degradation at the Patio de Los Leones, the core of the world-famous site of the Alhambra and Generalife, which attracts to Granada in Spain where they are located over 2 million tourists per year. The paper aims to define a new methodology to assess the level of urgency to restore the 124 columns of the Patio de Los Leones (Alhambra). It is not easy to identify all the factors affecting the columns' deterioration and to establish which should be restored first. Our approach is to collect all the data regarding the decay factor and use multi criteria decision aid methods such us the Analytic Hierarchy Process in order to create a hierarchy among all columns according to their decay. We also will create an HBIM model of the Patio del Los Leones in order to optimize the management and maintenance of the columns. HBIM model can also optimize the data management and enable to compare results (in this case data about columns decay) over time.